Physicochemical Analysis On Extrudates Made From By-Products Of Rice Milling Industry (Broken Rice And Bran) - Joko Hermanianto; Rizal Syarief; Zakiah Wulandari (Jurnal Teknologi dan Industri Pangan, 2000)
Extrudates were produced by double screw extrusion cooking under four barrel temperatures (29- 33oC, 29-33oC, 34-39oC, and 121-142oC)., feeder speed of 16- 17 rpm speed of knife of 425-713 rpm and ten formulations of corn, broken rice and bran. The physichochemical characteristics of the products were examined. Ash content, protein content and lipid content increased by increasing the percentage of the bran in formulation. Degree of gelatinization (DG). Expansion of extrudates (EE), Stickiness, Water solubility and absorbition indexes (WSI and WAI), colour of extrudates product (L and b ) decreased with increase in bran concentration.